(untitled) (The International Journal for Scientific Research, 2024)
Digital architecture has become popular in the second millennium, achieving architectural styles and approaches that are prevalent at present and reflect the latest trends, technologies, and design philosophies. Therefore, the term "contemporary architecture" may include a variety of styles and movements. In the second half of the twentieth century, some sufficient theories and proposals explored the possibilities of architecture as a language of social and technological development. This led to an "architecture crisis" and urban and environmental problems arising from the ideas of modernity. The research problem is a cognitive deficiency in the applications of parametric modeling in local architectural projects. The research aims to identify digital technologies in architectural design in global projects that have brought about intellectual and professional transformations in architecture, which have produced a series of new theories, technologies, and methods of construction in search of a "new paradigm" to solve the complex problems emerging in design and parametric applications in architectural projects.